Analysis of Compound Flooding in the Cakung Drain Area, DKI Jakarta Province - Nurabriansyah Rahman; Kusuma Muhammad Syahril Badri; Moerwanto Arie Setiadi (E3S Web of Conferences, 2024)
Cakung Drain is an artificial river located downstream of the Cakung and Buaran Rivers, established as part of Jakarta's flood control infrastructure. Administratively, the upper section of Cakung Drain is located in East Jakarta, while the lower section is in North Jakarta. The current capacity of Cakung Drain is insufficient to handle the flow during flood conditions, leading to persistent flooding in the area. Flood conditions downstream of Cakung Drain are exacerbated by the potential for Compound Flood, resulting from the simultaneous occurrence of two extreme conditions. Various initiatives to manage floods have been implemented in the Cakung Drain area. This study aims to evaluate the flood risk in the Cakung Drain area before and after the implementation of flood management structures, considering the impact of discharge and tidal conditions downstream influenced by waves and storm surges. Flood modelling is executed using HECRAS software employing both 1D and 2D approaches. The study's findings reveal that the flooded area under existing conditions spans 7.065 km2. Under design conditions, flooding persists with an area of 4.15 km², attributed to flood overflow in downstream areas where embankments have not been constructed.